2009
DOI: 10.1080/00018730903122242
|View full text |Cite
|
Sign up to set email alerts
|

Lattice symmetry breaking in cuprate superconductors: stripes, nematics, and superconductivity

Abstract: This article will give an overview on both theoretical and experimental developments concerning states with lattice symmetry breaking in the cuprate high-temperature superconductors. Recent experiments have provided evidence for states with broken rotation as well as translation symmetry, and will be discussed in terms of nematic and stripe physics. Of particular importance here are results obtained using the techniques of neutron and x-ray scattering and scanning tunneling spectroscopy. Ideas on the origin of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
587
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(603 citation statements)
references
References 534 publications
(587 reference statements)
12
587
1
3
Order By: Relevance
“…In this still SC state the filaments constitute snake-like paths through an SDW background with an average density of almost one electron per site. These textures provide a link to the study of disordered (quenched) stripes similar to those discussed recently within various GL models [35][36][37]. Therefore, depending upon the correlation strength and the details of the disorder, the magnetic ordering temperature T g can vary significantly, and the ordering itself can be droplet or filamentary-like.…”
mentioning
confidence: 59%
“…In this still SC state the filaments constitute snake-like paths through an SDW background with an average density of almost one electron per site. These textures provide a link to the study of disordered (quenched) stripes similar to those discussed recently within various GL models [35][36][37]. Therefore, depending upon the correlation strength and the details of the disorder, the magnetic ordering temperature T g can vary significantly, and the ordering itself can be droplet or filamentary-like.…”
mentioning
confidence: 59%
“…2,6,11,28,75 The detection of CO in bulk SC crystals with x far below and far above x = 1/8 is certainly the most significant finding. The full picture, however, becomes clear only when considering the relationship between the various properties and transition temperatures.…”
Section: Discussionmentioning
confidence: 95%
“…Among the debated interpretations is the so-called stripe model in which the charge carriers in the CuO 2 planes segregate into hole rich stripes, thus forming antiphase boundaries between intermediate spin stripes with locally AF correlations. 12,[26][27][28] In the LTT phase, which breaks the fourfold rotational symmetry of the individual CuO 2 planes, the electron-lattice coupling is believed to play a central role in the pinning of stripes, [29][30][31][32][33] although recent experiments under pressure revealed that stripes can break the symmetry even in the absence of long range LTT order. 34 So far, La 1.6−x Nd 0.4 Sr x CuO 4 is the only system with stripe-ordered LTT phase where magnetic and charge order have been studied with diffraction on both sides of x = 1/8.…”
Section: Introductionmentioning
confidence: 99%
“…Detwinned single crystals of YBa 2 Cu 3 O 6.51 (ortho-II, Tc = 57 K, doping concentration p ∼ 0.1) and YBa 2 Cu 3 O 6.67 (ortho-VIII, Tc = 67 K, p ∼ 0.12) were studied. We note that YBCO crystals generally belong to the cleanest available cuprate among the different families (31). The single crystals were obtained from flux growth (32).…”
Section: Methodsmentioning
confidence: 99%